Keterbatasan pengawas sekolah dalam meningkatkan mutu pendidikan di masa pandemi - Ngindana, Rispa; Ibnu Faruki, Adnan; Utami, Putri; Hermayanti, Tanti; Fergy Sandria, Muhammad; Nicolas, Hieronimus; Rahmawati, Yuli Nur (Lembaga Pendidikan Ma'arif Nahdlatul Ulama, Kabupaten Malang, Indonesia, 2022)
The role of school supervisors during this pandemic is felt to be less than optimal in the supervision process, this is because there are several limitations or obstacles experienced by school supervisors. Some of the inhibiting factors come from factors within the supervisor (internal factors) and also factors from outside the supervisor (external factors). To overcome the problem regarding the inhibiting factors for school supervisors in carrying out their duties, there are several solutions including providing allowances for supervisors who work in schools that are far away and also building a conducive organizational environment so that teachers are able to be open with school supervisors. The purpose of this case study article is to analyze what factors cause the role of school supervisors to be not optimal in the process of implementing their supervision, by knowing what factors influence them, we can provide suggestions or solutions regarding the school supervisor's problems, especially during the pandemic. The research method used is literature study, namely research whose sources come from journals, scientific articles, literature reviews containing the concepts and discussions under study.